2000
DOI: 10.1002/1098-2302(2000)37:4<253::aid-dev6>3.3.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

The effects of medial preoptic area and amygdala lesions on maternal behavior in the juvenile rat

Abstract: The present study was designed to determine whether the medial preoptic area (MPOA) and the amygdala (AMYG) are involved in the expression of "maternal" behavior in juvenile rats as they are in the adult. Juveniles show many behaviors that are similar to the maternal behaviors shown by the postpartum female rat. Whether these behaviors are social in function, as opposed to parental, and hence mediated by different mechanisms from those regulating adult maternal behavior is not known. To test the roles of the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In humans, the maternal behavioral repertoire includes gaze at infant face, 'motherese' highpitched vocalizations, expression of positive affect, affectionate touch, and the synchronous adaptation of these behaviors to moments of infant responsiveness (Barrett and Fleming, 2011;Feldman and Eidelman, 2007). Such human maternal behaviors parallel the licking-and-grooming and arched-back nursing of other mammals, which have been linked with the affiliation-related neuropeptide Oxytocin and the functioning of motivational and affective neural systems Lee et al, 2000;Oxley and Fleming, 2000;Shahrokh et al, 2010;Strathearn et al, 2009;Toscano et al, 2009). However, to date, little research examined the integration of brain circuits, affiliative hormones, and maternal behavior in human mothers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In humans, the maternal behavioral repertoire includes gaze at infant face, 'motherese' highpitched vocalizations, expression of positive affect, affectionate touch, and the synchronous adaptation of these behaviors to moments of infant responsiveness (Barrett and Fleming, 2011;Feldman and Eidelman, 2007). Such human maternal behaviors parallel the licking-and-grooming and arched-back nursing of other mammals, which have been linked with the affiliation-related neuropeptide Oxytocin and the functioning of motivational and affective neural systems Lee et al, 2000;Oxley and Fleming, 2000;Shahrokh et al, 2010;Strathearn et al, 2009;Toscano et al, 2009). However, to date, little research examined the integration of brain circuits, affiliative hormones, and maternal behavior in human mothers.…”
Section: Introductionmentioning
confidence: 99%
“…Lesions and DA manipulation studies (Li and Fleming, 2003) have demonstrated that the NAcc is critical for maternal behavior, particularly for maternal motivation to nest and retrieve pups Hansen, 1994;Hansen et al, 1991;Keer and Stern, 1999;Li and Fleming, 2003;Vernotica et al, 1999). The amygdala, a central node of the limbic affective system, has similarly been implicated in social affiliation and maternal attachment (Fleming and Korsmit, 1996;Lee et al, 2000;Oxley and Fleming, 2000). Lesions to the amygdala reduce maternal behavior (Toscano et al, 2009) and significant amygdala c-fos changes are observed following mother-pup interaction (Fleming and Korsmit, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Commercially available nestlets (NES3600, Ancare, Bellmore, NY, USA) were placed into cages (1 nestlet per cage) containing a dam and her litter on a single occasion between PN0 and PN2. Dams were allowed to shred the nestlet into a nest and thereafter nests were scored using a modified rating scale (Oxley & Fleming ) as follows: 1, nest material untouched; 2, nest material scattered (no nest formed); 3, very rough nest shape (no enclosing walls and gathered loosely); 4, definite nest formed (flat, enclosing walls but no bowl‐shape) and 5, definite spherical nest (enclosing walls and bowl‐shape). For nest construction, the following group sizes were used: 24 TPH2 +/+ and 22 TPH2 −/− dams with their own pups, 12 TPH2 +/+ dams with TPH2 −/− pups, 15 TPH2 −/− dams with TPH2 +/+ pups, 10 TPH2 −/+ and 11 TPH2 −/− dams with mixed litters.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, several studies have shown that lesions in the mPOA or the vBNST, as well as the impairment of the connectivity between the mPOA/vBNST and the mesolimbic dopaminergic system, abolish the expression of maternal behaviour. Based on these and other studies, Numan and Numan and Stolzenberg proposed that mPOA/vBNST efferents to the ventral tegmental area (VTA) facilitate dopaminergic inputs to the NA, which in turn release the ventral pallidum from the inhibitory influence of this nucleus, promoting the expression of voluntary maternal response towards pups .…”
Section: Introductionmentioning
confidence: 99%